SEJARAH DAN DINAMIKA MAJLIS TAFSIR AL-QUR’AN (MTA) DI SRAGEN JAWA TENGAH (1971-1993) - Muhammad Wildan; Oktavia Prastyaningrum (Fakultas Adab dan Ilmu Budaya UIN Sunan Kalijaga Yogyakarta, 2017)
Well known as a puritan Islamic movement identic with Muhammadiyah which opposes the Javanese traditions (Kejawen), Majlis Tafsir al-Qur’an (MTA) has spread quickly in many regions in Indonesia, including those strong with Javanese culture. Sragen regency is one of the areas of Surakarta that experienced the development of MTA quite rapidly. The rapid development of MTA can not be separated from the support of people who have long been the followers of Muhammadiyah. However, MTA also received negative responses from several groups, such as Nahdlatul Ulama (NU). All these dynamics is interesting to investigate. The research on MTA in Sragen is a historical study which employ sociology as an analytical tool. The tool helps researcher to reconstruct history by understanding influence of MTA for religious societies, emergence of disputes, and factors that support progress MTA by looking at social facts in Sragen. The result of this research indicates that condition of society greatly affect the development and dynamics of MTA in Sragen. MTA tends to grow rapidly in Muhammadiyah environment than its counterpart NU because it gets a hard challenge. But, some supporting factors, such as structural, financial, cultural, and social, greatly support the progress of MTA in Sragen